GEOLOGY AND GEOCHEMISTRY OF GUNUNG IJO AND SURROUNDINGS, KULONPROGO - PURWOREJO DISTRICT, YOGYAKARTA SPECIAL REGION - CENTRAL JAVA - FASIHAL RACHMAN, MUHAMMAD
The geological mapping was done on a field located at 393000 – 409000 mE, 9131000 – 9146000 mN UTM coordinate system, Kulonprogo – Purworejo district, Yogyakarta Special Region – Central Java. The purpose of this research is about to find out how the geological setting works such as geomorphology, stratigraphy, structural style, tectonic setting, magma series, and magma differentiation of these volcanics rock. Kulonprogo – Purworejo ridges has an elongated form used to called oblong dome, as part of South Serayu Ridges (van Bemmelen. 1949) that was made up by Tertiary magmatism and volcanic activity that has already wiped out and now it stands still as volcanic skeleton as the rest of old geomorphic stage (Soeria- Atmadja dkk. 1991). Four stratigraphic formations were lied down at this region listed form old to young such as Nanggulan Formation, Old Andesite Formation, Jongrangrang Formation and Sentolo Formation. Structural geology at this region controlled by couple of Kebumen – Muria and Bantul – Yogyakarta major sinistral faults. This region has settled down as a set of geomorphological, stratigraphic and structural units. Geomorphological units on this region has set up as anticline dome, volcanic denudation hills, volcanic skeleton hills, karst tower, karst conical hills, karst plain, denudation valley, and flood plain. Lithostratigraphic units that lied down at this region listed as sandstone, pyroxene-andesite intrusion, quartzandesite lava, hornblende-andesite lava, volcanic breccia, interbedded limestone-mudstone, reef boundstone, interbedded mudstone-sandstone, clastic limestone and alluvium bar. Structural geology that operated at this region compromise as anticline dome, sinistral faults and dextral faults. Methodology of this study case consist of two parts, petrographic analysis such as major texture, plagioclase-microtexture, mineralogy distributions, and calculation of geochemistry data that use Harker diagrams, silica saturation, discriminants and spiderdiagrams. Seven samples was used at this case that was picked up at few locations called Kalisonggo, Kalibuko, Kalirejo, Kukusan Mount, Suru Mount, Ijo Mount, and Sermo River. The results of those analysis showed that volcanic rocks at this region form at subduction tectonic setting, calc-alkaline magma series, and then magma differentiation process that had happened such as crystal fractionation, magma mixing, and magma assimilation.